Strategi Meningkatkan Kualitas Koperasi di PT PNM Mekar Syariah Nagari Padang Lua Kecamatan IV Koto Kabupaten Agam - Nur Laila; Ali Rahman (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze strategies for improving the quality of Islamic cooperatives at PT PNM Mekar Syariah in Nagari Padang Lua, IV Koto District, Agam Regency. Islamic cooperatives play a strategic role in empowering communities, particularly underprivileged women; however, in practice they still face various challenges related to institutional quality, service performance, and member discipline. This research employed a qualitative descriptive approach. Data were collected through interviews, observation, and documentation involving cooperative staff, members, and community figures. The data were analyzed using qualitative techniques through data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings show that the quality of the cooperative at PT PNM Mekar Syariah Nagari Padang Lua has not yet reached an optimal level, as indicated by limited product diversification, insufficient human resource competence, and delays in financing repayments by some members. To address these issues, the cooperative has implemented strategies including member coaching, capacity building for staff, and strengthening supervision and financing management systems. These strategies have contributed to reducing the number of problematic members, although further improvement is still needed, particularly in product diversification and managerial professionalism. This study provides empirical evidence for the development of Islamic cooperatives as sustainable and inclusive microfinance institutions.